Gradual Pre-eruptive Phase of Solar Coronal Eruptions - Vršnak, Bojan (Frontiers in Astronomy and Space Sciences, 2019)
Physical background of the evolution of a coronal magnetic flux rope embedded in the magnetic arcade during the gradual-rise pre-eruptive stage is studied. It is assumed that this stage represents an externyly-driven evolution of the preeruptive structure through a series of quasi-equilibrium states, until a point when system losses equilibrium and erupts. In particular, three driving processes are considered: twisting motions of the flux-rope footpoints, emergence of new magnetic flux beneath the flux rope, and the mass leakage down the flux-rope legs. For that purpose, an analytical flux-rope model is employed, to inspect how fast the equilibrium height of the structure rises due to the increase of the poloidal-toaxial field ratio, the increase of axial electric current, and the decrease of mass. It is shown that the flux-rope twisting itself is not sufficient to reproduce the rising speeds observed during the pre-eruptive stage. Yet, it is essential for the loss-ofequilibrium process. On the other hand, the considered emerging flux and the mass loss processes reproduce well the rate at which the pre-eruptive structure rises before the main acceleration stage of the eruption sets in.